Malignant melanoma of soft parts with osteoclast-rich giant cells: A rare tumour of the jejunum - Mallick, Saumyaranjan (Australasian Medical Journal, 2014)
Malignant melanoma of soft parts (MMSP), first described by Franz M. Enzinger, is a rare tumour of unknown cell origin. We describe a case of a 45-year-old male who presented with a one-year history of abdominal pain, weakness, and anaemia. Computerised tomography enteroclysis showed a mass in the jejunum that was suggestive of a gastrointestinal stromal tumour. An ulceroinfiltrative lesion measuring 6.5 x 4 x 2cm was identified. Microscopy revealed typical features of MMSP with numerous osteoclasts-like giant cells. The diverse histomorphology and immunohistochemical characteristics of this case involving a rare tumour at a rare site is presented.